Hyaluronan-CD44 interactions mediate contractility and migration in periodontal ligament cells. Issue 1 (1st January 2019) - Al-Rekabi, Zeinab; Fura, Adriane M.; Juhlin, Ilsa; Yassin, Alaa; Popowics, Tracy E.; Sniadecki, Nathan J.
ABSTRACT: The role of hyaluronan (HA) in periodontal healing has been speculated via its interaction with the CD44 receptor. While HA-CD44 interactions have previously been implicated in numerous cell types; effect and mechanism of exogenous HA on periodontal ligament (PDL) cells is less clear. Herein, we examine the effect of exogenous HA on contractility and migration in human and murine PDL cells using arrays of microposts and time-lapse microscopy. Our findings observed HA-treated human PDL cells as more contractile and less migratory than untreated cells. Moreover, the effect of HA on contractility and focal adhesion area was abrogated when PDL cells were treated with Y27632, an inhibitor of rho-dependent kinase, but not when these cells were treated with ML-7, an inhibitor of myosin light chain kinase. Our results provide insight into the mechanobiology of PDL cells, which may contribute towards the development of therapeutic strategies for periodontal healing and tissue regeneration.